Citizen Science and Biological Invasions: A Review - Encarnação, João; Teodósio, Maria Alexandra; Morais, Pedro (Frontiers in Environmental Science, 2021)
Biological invasions are among the most challenging ecological and conservation riddles of our times. Fortunately, citizen science projects became a valuable tool to detect non-indigenous species (NIS), document their spread, prevent dispersion, and eradicate localized populations. We evaluated the most consensual definitions of citizen science and proposed that a combination of two of them is a better reflection of what citizen science has become. Thus, citizen science is any environmental and/or biological data collection and analysis, including data quality control, undertaken by members of the general public, as individuals or as organized groups of citizens, with the guidance and/or assistance of scientists towards solving environmental and/or community questions. With this review, we also assessed how citizen science has been advancing biological invasions research and its focus, by analyzing 126 peer-reviewed articles that used citizen science methods or data concerning NIS. Most of the articles studied terrestrial species (68%) and terrestrial plants were the most studied group (22.7%). Surprisingly, most first detection reports were of non-indigenous marine fish probably due to the constraints in accessing aquatic ecosystems which delays the detection of new NIS. Citizen science projects running over broad geographical areas are very cost-effective for the early detection of NIS, regardless of the studied environment. We also discuss the applicability and need to adapt the methods and approaches towards the studied ecosystem and species, but also the profile of the participating citizens, their motivations, level of engagement, or social status. We recommend authors to better acknowledge the work done by contributing citizens, and the putative limitations of data generated by citizen science projects. The outreach planning of citizen science projects is also evaluated, including the use of dedicated web platforms versus pre-existent and disseminated web platforms, while discussing how such outreach actions can be maximized. Lastly, we present a framework that contextualizes the contributions of citizen science, scientific research, and regional and national stakeholders towards the integrated management of biological invasions.